2019
DOI: 10.1186/s40425-019-0739-1
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular NK histones promote immune cell anti-tumor activity by inducing cell clusters through binding to CD138 receptor

Abstract: BackgroundNatural killer (NK) cells are important anti-tumor cells of our innate immune system. Their anti-cancer activity is mediated through interaction of a wide array of activating and inhibitory receptors with their ligands on tumor cells. After activation, NK cells also secrete a variety of pro-inflammatory molecules that contribute to the final immune response by modulating other innate and adaptive immune cells. In this regard, external proteins from NK cell secretome and the mechanisms by which they m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…Another crucial immunoregulatory role of NK cells for T cells has been observed by us in the context of tumor cells, but in this case, NK cells stimulate T cell activity. We found that NK cells, by releasing pro-inflammatory molecules, such as histones, promote the anti-tumor activity of T cells by accelerating T cell/tumor cell cluster formation [106]. All these studies showing the immunoregulatory role performed between NK cells and T cells should be considered in immunotherapy to find a balance between both immune populations, as both are required to eliminate tumor cells in an efficient manner.…”
Section: Coordinated Immune Response After Viral Infectionsmentioning
confidence: 71%
See 3 more Smart Citations
“…Another crucial immunoregulatory role of NK cells for T cells has been observed by us in the context of tumor cells, but in this case, NK cells stimulate T cell activity. We found that NK cells, by releasing pro-inflammatory molecules, such as histones, promote the anti-tumor activity of T cells by accelerating T cell/tumor cell cluster formation [106]. All these studies showing the immunoregulatory role performed between NK cells and T cells should be considered in immunotherapy to find a balance between both immune populations, as both are required to eliminate tumor cells in an efficient manner.…”
Section: Coordinated Immune Response After Viral Infectionsmentioning
confidence: 71%
“…Of note, we have also observed that CB-NK [11] release histones with anti-fungal in vitro and in vivo activity against Candida albicans (unpublished data). Moreover, this immunomodulatory role for NK cell histones was also observed in a tumor context, where histones released by NK cells were able to recruit T cells to perform anti-tumor activity [106].…”
Section: Nk Cells Alone and In Collaboration To Fight Fungal Infectionsmentioning
confidence: 85%
See 2 more Smart Citations
“…Recently, it has been identified that IFNγ and TNFα, two cytokines highly secreted after cell immunotherapy [ 85 ], induce senescence in different murine and human neoplastic diseases [ 86 ]. Moreover, we observed that natural killer (NK) cells, which are used as a source for immunotherapy [ 87 ], secrete a high variety of proinflammatory molecules, including matrix metalloproteases, heat shock proteins [ 88 ] and others present in the SASP.…”
Section: Senescence In Cancermentioning
confidence: 99%